Can microinsurance help prevent child labor? An impact evaluation from Pakistan - Andreas Landmann; Markus Frölich (Institute for the Study of Labor (IZA), 2013)
Child labor is a common consequence of economic shocks in developing countries. We show how reducing vulnerability can affect child labor and schooling. We exploit the extension of a health and accident insurance scheme by a Pakistani microfinance institution (MFI) that was set up as a randomized controlled trial and accompanied by household panel surveys. Together with increased coverage the MFI offered assistance with claim procedures in treatment branches. Using Difference-in-difference techniques we find lower incidence of child labor and lower child labor earnings caused by the innovation. Separating the two parts of the innovation package, the effects of claim assistance are mostly insignificant, while increased insurance coverage has large effects on child labor outcomes and days missed at school. Consistent with a theoretical model we develop in this paper, the effect is largely due to an ex-ante feeling of protection as opposed to a shock-mitigation effect.
Keywords: I13; J20; J82; O12; 330; child labor; health insurance; Pakistan